Highlights of Factors of Adolescent gender Disorders "Like Thorns in The Flesh" - Mahmud, Maisarah; Zainatul Nadra Zainol , Nur (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
The problem of gender confusion has existed for a long time and it is becoming more prevalent in Malaysia. Various approaches have been taken to curb this problem from spreading. This symptom of gender confusion has been one of the factors to the phenomenon of Lesbian, Gay, Bisexual and Transgender (LGBT) which is at odds with Islam and eastern culture. Facts show that the involvement of the LGBT community is becoming more and more worrying in society, in fact, this symptom is becoming more contagious not only among adults but also affects teenagers who are still in school. However, there are still insufficient studies which systematically review the literature that touches on the root causes of the problems to the occurrence of this gender confusion. Therefore, this article conducts a systematic review of the literature on the factors of occurrence of gender confusion problems. This study selected articles using two major databases namely Scopus and Google Scholar. The results of the study found that there are three main factors in the occurrence of this gender confusion problem, including lack of religious knowledge, family factors, environmental factors and past experience factors. For future studies, it is recommended to use different systematic survey methods and use additional databases. environmental factors and past experience factors. For future studies, it is recommended to use different systematic survey methods and use additional databases. environmental factors and past experience factors. For future studies, it is recommended to use different systematic survey methods and use additional databases